ER Stress–Related Genes EIF2AK3, HSPA5, and DDIT3 Polymorphisms are Associated With Risk of Lung Cancer - Liu, Yongshi; Liang, Xiaohua; Zhang, Hongpei; Dong, Jiajia; Zhang, Yan; Wang, Juan; Li, Chunmei; Xin, Xiangbing; Li, Yan (Frontiers in Genetics, 2022)
Objective: This study aimed to evaluate the associations between endoplasmic reticulum (ER) stress related genes EIF2AK3/PERK, HSPA5/GRP78 and DDIT3/CHOP polymorphisms and risk of lung cancer. Methods: Six single nucleotide polymorphisms (SNPs) of EIF2AK3, HSPA5 and DDIT3 were genotyped in 620 cases and 620 controls using a MassARRAY platform. Results: The minor allele A of rs6750998 was a protective allele against the risk of lung cancer (p <0.001), while the minor alleles of rs867529, rs391957 and rs697221 were all risk alleles that may lead to multiplied risk of the disease (rprs867529 = 0.002; prs391957 = 0.015; prs697221 <0.001). Moreover, the rs6750998-TA/AA genotypes were protective genotypes against the risk of lung cancer (p = 0.005); however, the rs867529-GC/CC, rs391957-CC and rs697221-GA/AA genotypes were associated with elevated lung cancer risk (prs867529 = 0.003, prs391957 = 0.028, prs697221= 0.0001). In addition, EIF2AK3-rs6750998 was associated with a decreased risk of lung cancer under dominant, recessive and log-additive models (p <0.05). By contrast, the EIF2AK3-rs867529 was correlated with an increased risk of the disease under dominant and log-additive models (p = 0.001). Moreover, HSPA5-rs391957 was related to an elevated risk of the disease under recessive and log-additive models (p <0.02). DDIT3-rs697221 was identified had significant association with risk of lung cancer under all three genetic models (p <0.01). Conclusion: Our results provided new insights on the role of the ER stress related genes EIF2AK3, HSPA5 and DDIT3 polymorphisms for lung cancer risk.